2019
DOI: 10.3390/ma12213615
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Powder Concrete Mix Ratio and Steel Fiber Content Optimization under Different Curing Conditions

Abstract: In this paper, a practical reactive powder concrete mixture ratio is created on the basis of an orthogonal experiment. Previous studies have combined the compressive and splitting tensile strengths of four categories of reactive powder concrete (RPC) for major materials. These categories include water/binder ratio, silica fume volume content, sand/binder ratio, and dosage of fly ash volume. The optimal mixing proportion of each factor was determined by analyzing the compressive strength of the RPC matrix. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The results showed that the splitting tensile strength increased from 4.033 to 9.609, 11.944, and 12.896 MPa, respectively when the steel fiber increased from 0% to 1%, 1.5%, and 2% [23]. The results showed that with the content of steel fiber from 0% to 4%, the compressive strength and splitting tensile strength are increased, and the compressive strength of steel fiber to RPC is increased less, and the splitting tensile strength is obviously improved [20,24]. Moreover, the effect of incorporation of different types of steel fibers on the mechanical properties of the RPC is also different.…”
Section: Introductionmentioning
confidence: 91%
“…The results showed that the splitting tensile strength increased from 4.033 to 9.609, 11.944, and 12.896 MPa, respectively when the steel fiber increased from 0% to 1%, 1.5%, and 2% [23]. The results showed that with the content of steel fiber from 0% to 4%, the compressive strength and splitting tensile strength are increased, and the compressive strength of steel fiber to RPC is increased less, and the splitting tensile strength is obviously improved [20,24]. Moreover, the effect of incorporation of different types of steel fibers on the mechanical properties of the RPC is also different.…”
Section: Introductionmentioning
confidence: 91%
“…e specific surface area of the steel and basalt fibers is large, and the basalt fibers have a rough surface and high friction coefficient, which increase internal friction resistance and worsen the fluidity of the mixture. A large amount of cement paste is attached to the surface of the hybrid fibers, and the cement paste wrapped around the manufactured sand is reduced [8], thereby increasing the viscosity of the mixture and decreasing workability. With the same amount of steel fibers (A), slump is slightly reduced as the amount of the basalt fibers (B) increases.…”
Section: Workability Of Rpcmentioning
confidence: 99%
“…Compared with the nonfiber RPC, the flexural strength of the mixed RPC is improved obviously, because the main factor affecting flexural strength is the bonding force between the fibers and the matrix. In the loading process, because the fibers demonstrate roughness and unevenness, the fibers slip with the matrix under tension and produce adhesion stress, which plays a bridging role and hinders the development of cracks [8], thereby substantially enhancing flexural strength. Given that the RPC hydration reaction at 7 days is incomplete and the bond between the fibers and the matrix is not at its maximum, pulling the fibers out during the bending resistance experiment is easy.…”
Section: Flexuralmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the authors of this paper, it can be concluded on this basis that the creation of concrete composite structures with RPC is a particularly beneficial way to use it in practice for both the manufacture of precast elements and the strengthening of the existing ones. Creating OC-RPC composite structures instead of structures made only of RPC is justified in view of the need to reduce costs and carbon footprint due to increased binder consumption and the higher technological requirements for RPC production (e.g., according to [39], the cost of RPC with a strength of 90-140 MPa compared to OC with a compressive strength of 30-60 MPa is approx. 3-5 times higher).…”
Section: Introductionmentioning
confidence: 99%